2021
DOI: 10.20343/teachlearninqu.9.2.20
|View full text |Cite
|
Sign up to set email alerts
|

Increase Engaged Student Learning Using Google Docs as a Discussion Platform

Abstract: Online discussion board activities have traditionally been a primary method of providing student-to-student interaction, especially in asynchronous online classes. This study examines the impact of an alternate online discussion tool on student participation in online discussion assignments. Three identical discussion assignments were examined over the course of two semesters. The first semester utilized the traditional Learning Management System (LMS) threaded discussion board. The second semester incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
3
3
0
Order By: Relevance
“…Hence, the average number of posts shared per student in the Google Docs group was 38% higher than the average number of posts shared per student in the discussion forum group. This result was in accordance with Morse (2021) who found that the number of contributions by the Google Docs' students outperformed those provided by the discussion forum group by 68% in three discussion topics.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Hence, the average number of posts shared per student in the Google Docs group was 38% higher than the average number of posts shared per student in the discussion forum group. This result was in accordance with Morse (2021) who found that the number of contributions by the Google Docs' students outperformed those provided by the discussion forum group by 68% in three discussion topics.…”
Section: Discussionsupporting
confidence: 91%
“…However, they found it tedious and challenging in terms of following and reading a high number of threads of discussions. This result agreed with Gao et al (2013) and Morse (2021) who highlighted some constraints of using discussion forums in collaboration if compared to Google Docs. They believed that the structure of Google Docs encouraged participation since all the comments and revisions were included in the same document and no need to review tens of posts or follow a high number of conversation threads one at a time.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations